2022
DOI: 10.1097/md.0000000000031651
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of caffeine consumption behavior among Jazan University students in the south of Saudi Arabia: A cross-sectional study

Abstract: Caffeine is a central nervous system stimulant. High consumption levels of caffeine can lead to intoxication and serious side effects. Saudi Arabia is witnessing a rise in the commercialization and consumption of caffeine. Young adults such as university students may exhibit high levels of caffeine consumption. This investigation aims to assess caffeine consumption habits among a sample of Jazan University students in the south of Saudi Arabia. This study was a cross-sectional investigation that utilized multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, there are still concerns about the elevated levels of caffeine consumption among the youth in Saudi Arabia, despite these measures. [16]…”
Section: Pharmacological Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are still concerns about the elevated levels of caffeine consumption among the youth in Saudi Arabia, despite these measures. [16]…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…The data also revealed that the year of study was the only demographic variable that had a statistically significant association with caffeine consumption (p value of 0.003). [16] This implies that students who are in their first few years of college or university are more likely to consume more caffeine than the recommended daily limit, as they face the stress of adjusting to a new environment and learning style. In contrast, students in their later years of study may be more accustomed to the academic demands and less likely to exceed the recommended caffeine intake.…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Coffee and tea are the most popular natural caffeinated beverages. Additionally, soft drinks such as cola and energy drinks are also considered stimulant products [2]. Energy drinks typically contain higher concentrations of amino acids and herbals than those naturally found in food and plants.…”
Section: Introductionmentioning
confidence: 99%
“…People use caffeinated drinks for a variety of reasons. One reason is to enhance mental alertness by improving brain function, wakefulness, and productivity [2]. Energy drinks are commonly used by tired individuals to help them stay focused, but this may lead to a decrease in sleep quality [4].…”
Section: Introductionmentioning
confidence: 99%
“…al. 2023, Alfaifi, 2023, Aldogiher, 2023. The focal issue pertains to comprehending the degree to which the incorporation of health care insurance functions as a mediator, impacting the relationship between hospital management techniques and results related to operational efficiency (Alshahrani, 2023).…”
Section: Introductionmentioning
confidence: 99%